Fractography and Tensile Properties of AA6061 Aluminium Alloy/Rice Husk Ash Silicon Nanocomposite - N. E. Udoye; O. S. I. Fayomi; A. O. Inegbenebor (International Journal of Chemical Engineering)
The unstoppable quest for low-cost reinforcing agent gingered the enthusiasm towards developing and utilising the agro-based waste product as reinforcement since they are promptly accessible, sustainable, and inexpensive to purchase. In this study, AA6061/rice husk ash matrix composites were produced through metallurgical stir casting techniques. Different weight percentages of reinforcement in the range of 2%, 4%, 6%, and 8% were used to fabricate the composites. The reinforced composites were characterized by SEM/EDS for microstructural study. The mechanical behaviour was examined for all the produced samples. SEM/EDS analysis revealed the presence of silica, a major constituent of rice husk ash in the produced composites. The results of the mechanical behaviour show that upgrading the weight percentage of reinforcing agent increases the mechanical properties. AA6061/8% rice hush ash generated a consistent rise with filler concentration in comparison with the aluminium alloy in all operating functions.